Dziecięce konfabulacje i rozwój moralny najmłodszych - Grzesiak, Emilia (Studia Edukacyjne, 2023)
The article is devoted to the issue of children’s confabulations, which often characterize preschool children and constitute a specific part of this developmental period. The text explains the phenomenon of confabulation, who else it may concern, and why younger children fantasize and tell untrue stories. It will also discuss the topic of lies, the causes of insincerity among children, and the broadly understood moral development of the youngest.